POLITIK HUKUM PEMBENTUKAN DELIK PERMUFAKATAN JAHAT DALAM TINDAK PIDANA KORUPSI - Tantri Kartika (The Juris, 2018)
Criminal Agreement Crimes in the Criminal Code are regulated in Article 110 paragraph (1) to paragraph (4). Same spanning is specifically regulated, namely only against crimes as stipulated in Articles 104, 106, 107 and 108 of the Indonesian Criminal Code, meaning that criminal acts cannot be applied to all criminal acts contained in the Criminal Code, so they are exclusive (exceptions) as stated in Article 110 of the Criminal Code. Looking at the form of this evil agreement the question arises, why should the consensus on the provisions in Articles 104, 106, 107 and 108 of the Criminal Code be punished? This is because lawmakerssee crimes (crimes) as stipulated in Articles 104, 106, 107 and 108 of the Criminal Code that they have been seen as serious crimes and very dangerous especially for the safety of the State. Therefore, a crime called crime against the safety of the State must be prevented or eradicated at the time the crime is still at the level of preparation or still at the voorbereidings stadium.